Numerical Performance Simulations of Four-Wheeled Cruise-controlled Vehicle on Road Surface - Patriawan, Desmas Arifianto; Arifin, Ahmad Anas; Pramujati, Bambang (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2023)
Cruise control (CC) has started to be widely used in cars, making driving easier for a long time. However, in designing the control system on the CC, it is also necessary to perform performance testing, so that the CC can achieve the desired speed accurately and comfortably. The approach employed in this paper involves creating a numerical model design based on CC and subsequently assessing its performance through simulations with varying levels of resistance. Variation of resistance given is by road conditions (rolling resistance) and drag coefficient. The test outcomes, when subjected to changes in road surface conditions, demonstrate that CC remains capable of achieving a rapid response time and maintaining a consistent steady-state error of approximately 2.01%. Despite minimal variations observed in the drag coefficient test, the CC-designed model remains dependable in accommodating alterations in road surface and discrepancies in drag coefficients. Furthermore, the resultant vehicle acceleration does not exceed 2G, ensuring passenger comfort is not compromised.